2021
DOI: 10.3389/fbioe.2020.536957
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Modeling Combined With Machine Learning Integrates Longitudinal Data and Identifies the Origin of LXR-Induced Hepatic Steatosis

Abstract: Temporal multi-omics data can provide information about the dynamics of disease development and therapeutic response. However, statistical analysis of high-dimensional time-series data is challenging. Here we develop a novel approach to model temporal metabolomic and transcriptomic data by combining machine learning with metabolic models. ADAPT (Analysis of Dynamic Adaptations in Parameter Trajectories) performs metabolic trajectory modeling by introducing time-dependent parameters in differential equation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A commonly used approach with dynamic models is L1 or Tikhonov regularization, which adds a penalty on parameters that deviate from a specific value, favoring the estimates that resemble experimental measurements [124][125][126][127]. Furthermore, to deal with big scale kinetics models, multiple toolboxes have been developed that assist in the development and analysis of this large-scale models [128][129][130][131], and benchmarking studies have evaluated their performance in different setups [14,132], which will help the modeler select the tool that is best suited for a particular problem.…”
Section: Chen Et Al [118] Smallbone Et Al [16] Kesten Et Al [20]mentioning
confidence: 99%
“…A commonly used approach with dynamic models is L1 or Tikhonov regularization, which adds a penalty on parameters that deviate from a specific value, favoring the estimates that resemble experimental measurements [124][125][126][127]. Furthermore, to deal with big scale kinetics models, multiple toolboxes have been developed that assist in the development and analysis of this large-scale models [128][129][130][131], and benchmarking studies have evaluated their performance in different setups [14,132], which will help the modeler select the tool that is best suited for a particular problem.…”
Section: Chen Et Al [118] Smallbone Et Al [16] Kesten Et Al [20]mentioning
confidence: 99%
“…The authors identified fructokinase as a molecular target of the fructose pathway and predicted its suppression would revert lipid accumulation. Van Riel et al. (2020) used instead a machine learning algorithm, informed by metabolomic and transcriptomic time-series, to predict the metabolic response induced by treatment with a Liver X Receptor (LXR) agonist.…”
Section: Future Perspectivesmentioning
confidence: 99%
“… 335 These findings were paralleled by an increase of Abca1 mRNA and ABCA1 protein content, 335 suggesting a potential relevance of TO901217 in AD therapy, although it must be taken into account that LXR activators, in particular TO901317, were demonstrated to have severe side effects in mice, such as neutropenia, hypertriacylglycerolemia, hepatic triacylglycerol accumulation, and hepatic steatosis. 271 , 346 , 347 …”
Section: Part I: Status Quomentioning
confidence: 99%